2014
DOI: 10.3389/fmicb.2014.00028
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of nitrifying, anammox and denitrifying bacteria in a sequencing batch reactor

Abstract: Elevated nitrogen removal efficiencies from ammonium-rich wastewaters have been demonstrated by several applications, that combine nitritation and anammox processes. Denitrification will occur simultaneously when organic carbon is also present. In this study, the activity of aerobic ammonia oxidizing, anammox and denitrifying bacteria in a full scale sequencing batch reactor, treating digester supernatants, was studied by means of batch-assays. AOB and anammox activities were maximum at pH of 8.0 and 7.8–8.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 67 publications
8
35
0
Order By: Relevance
“…A previous study reported that b-subclass Proteobacteria played a key role in the activated sludge for nitrogen removal (Lee et al, 2002), which could contribute to both organic matter degradation and nitrogen removal. This also agrees with the nitritationanammox biomass which was characterized with a high diversity of denitrifiers of b-Proteobacteria (Langone et al, 2014). The bsubclass Proteobacteria (denitrifiers) played an important role in both anammox-nitrification and anammox-denitrification processes.…”
Section: Microbial Community Of the Sad Processsupporting
confidence: 72%
“…A previous study reported that b-subclass Proteobacteria played a key role in the activated sludge for nitrogen removal (Lee et al, 2002), which could contribute to both organic matter degradation and nitrogen removal. This also agrees with the nitritationanammox biomass which was characterized with a high diversity of denitrifiers of b-Proteobacteria (Langone et al, 2014). The bsubclass Proteobacteria (denitrifiers) played an important role in both anammox-nitrification and anammox-denitrification processes.…”
Section: Microbial Community Of the Sad Processsupporting
confidence: 72%
“…Our previous work had also detected the two kinds of NOB, i.e., Nitrobacter and Nitrospira, in this process of the nitrate build-up and the following in situ restoration by quantifying their 16S rRNA genes, 9 the results showed that the abundance of Nitrobacter was relatively stable at 2.0% throughout this process while the abundance of Nitrospira uctuated in the range of 5.21% to 2.34%. The similar situation had also occurred in the research by Langone et al, 24 where the primers targeting the 16S rRNA of Nitrobacter-like NOB yielded products of the correct size (225 nt), while no PCR products were obtained using the primers targeting the nxrA gene of Nitrobacter spp. The discrepancy of the NOB abundances based on the detections of 16S rRNA and nxrA gene might be attributed to that the nxrA gene containing cell numbers were too low and the other two of nxrB and nxrC genes functioned much in the nitrate build-up process.…”
Section: Response Of Functional Genessupporting
confidence: 74%
“…The inhibition of anammox activity was reported to occur at pH values <5, while high anammox activity was observed between pH values of 6 and 8 [112]. Similarly, another study reported that anammox worked best in a pH range of 7.8-8.0 [78]. This finding is also supported by other researchers who observed anammox activity only between pH values of 6.5 and 8.8, with an optimum pH of 8 [111,113].…”
Section: Phsupporting
confidence: 46%
“…In previous studies, researchers successfully cultivated anammox bacteria in suspended and attached growth types of bioreactors that were specifically designed to address the slow growing bacteria. The suspended-type bioreactors includes the sequencing batch reactor (SBR) [10], [78][79][80][81], UASB [49,52,58,76], membrane bioreactor (MBR) [13], anaerobic membrane bioreactor (AnMBR) [5] and the gas-lift reactor [82,83]. The attached growth-type bioreactors, including the FBR [35], rotating biological contactor (RBC) [84] and upflow biofilter (UBF) [85], use supporting material to retain the anammox microbial population.…”
Section: Anammox Enrichment In Bioreactor Systemsmentioning
confidence: 99%